Perfil de quimiocinas e citocinas séricas em recém-nascidos com diferentes manifestações da toxoplasmose congênita ocular - Araújo, Thádia Evelyn de (2016)
This study describes the first changes signatures and networks of chemokines and cytokines serum of patients with congenital toxoplasmosis infants (TOXO), compared to non infected controls (NI). TOXO group was divided according to retinochoroidal injury status: without injuty (SL), active injury (RA), scar and active injury (RAC) and scar injury (RC). The author found out that TOXO displays an outstanding profile of chemokine mediated by IL-8/CXCL8, MIG/CXCL9, IP-10/CXCL10 e RANTES/CCL5. WHILE il-8/cxcl8 AND ip-10/cxcl10 are general biomarkers associated with ocular injury MIG/CXCL9 appears with an active selection biomarker for retinlchoroidal injury. Furthermore, TOXO is characterized by a mixed pattern of cytokines with proinflamatory/regulatory action mediated by IL-6, IFN-, IL-4, IL-5 e IL-10. While TNF appears as a putative biomarker for SL and IFN-e IL-5 as immunological characteristic of RA, IL-10 appears as an important mediator in RAC/RC. Signatures of serum biomarkers confirm that TOXO is accompanied by a significant storm of chemokines/cytokines with a wide range of proinflamatory/regulatory mediators. IL-8/CXCL8 e IP-10/CXCL10 are indicators of broad ocular disease spectrum, while TNF is a biomarker for SL, IFN- and MIG/CXCL9 point for RA and IL-10 is highlighted as an excellent serum biomarker of ACRL/CRL. In the RA network a clear shortening neighboring connections are observed, while SL and CR showed a balanced network, as it was observed in NI. This network balancing, however, similar to the one observed in NI is supported by a signature of chemokines/cytokines in separate SL and CR. Thus, we concluded that infants infected with T. gondii produce a wide range of biomarkers that characterize the different types of toxoplasmosis lesion, which may assist in prognosis and diagnosis of the disease.